2003
DOI: 10.1016/s0896-6273(03)00287-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Neuronal Discharges that Increase Coding Efficiency during Perceptual Discrimination

Abstract: During a sensory discrimination task, the responses of multiple sensory neurons must be combined to generate a choice. The optimal combination of responses is determined both by their dependence on the sensory stimulus and by their cofluctuations across trials-that is, the noise correlations. Positively correlated noise is considered deleterious, because it limits the coding accuracy of populations of similarly tuned neurons. However, positively correlated fluctuations between differently tuned neurons actuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
158
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(171 citation statements)
references
References 29 publications
11
158
0
Order By: Relevance
“…Perceptual decision-making both in the visual and somatosensory domains has emphasized the existence of at least two stages in stimulus processing leading to stimulus discrimination; mainly a bottom up process followed by higher-level involvement of areas responsible for perceptual decision-making Romo et al, 2003;Salinas et al, 2000). Our results confirm the existence of at least two stages leading to perceptual decision across sensory modalities.…”
Section: Comparison To Existing Literaturesupporting
confidence: 79%
See 1 more Smart Citation
“…Perceptual decision-making both in the visual and somatosensory domains has emphasized the existence of at least two stages in stimulus processing leading to stimulus discrimination; mainly a bottom up process followed by higher-level involvement of areas responsible for perceptual decision-making Romo et al, 2003;Salinas et al, 2000). Our results confirm the existence of at least two stages leading to perceptual decision across sensory modalities.…”
Section: Comparison To Existing Literaturesupporting
confidence: 79%
“…During a vibrotactile discrimination experiment, single-unit recordings in somatosensory cortex predicted whether monkeys could perceive a difference in the stimulation frequency (Salinas et al, 2000). In the same kind of tasks, Romo et al (Romo et al, 2003) demonstrated the role of medial prefrontal and premotor cortices in forming the decision initially driven by evidence in somatosensory areas (see also de Lafuente and Romo, 2005;Hernandez et al, 2002). The same pattern of sequential stages has been repeatedly shown in the visual domain.…”
Section: Introductionmentioning
confidence: 76%
“…Thus, correlated activity serves to select the relevant population of neurons, as proposed for perceptual discriminations tasks (43)(44)(45). Furthermore, judicious processing of correlated signals can lead to the removal of common sources of fluctuations (46). Within this scenario, the modulation in coherence found in the present work provides a means to generate a reliable motor command that influences the heading and locomotion of the animal based on the saliency of environmental cues.…”
Section: Discussionmentioning
confidence: 79%
“…Correlation may be helpful or harmful depending on stimulus statistics, noise statistics, population size, and decoding mechanisms (25)(26)(27)(28)(29)(30)(31). Here we focus on how correlations influence two primary functions of spike trains: encoding information and propagating activity to downstream neurons.…”
mentioning
confidence: 99%
“…Correlated spiking facilitates propagation (30,(32)(33)(34). However, these correlations reduce the available repertoire of population activity patterns (31,35,36), thereby potentially impairing sensory discriminations (27). Because correlations can impact propagation and encoding in opposing ways, how do networks structure their correlations?…”
mentioning
confidence: 99%